2021
DOI: 10.7759/cureus.14263
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Management of Diabetic Hand Infections

Abstract: Purpose For many providers, hand infections among diabetic patients is a condition that necessitates focused inpatient care. These patients are believed to have decreased innate immunity to fight infection, a more virulent course, and difficulty with recovery. Diabetes is considered by some to represent an additional risk factor that can result in an unfavorable outcome if not managed in an aggressive manner. Our own experience suggests that many of these patients can be safely managed in the outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, these indexes use different ICD codes for diabetes with and without complications. In a cohort of diabetic and nondiabetic hand infections treated as outpatients, Qasawa et al found a low rate of outpatient failure [ 14 ]. Their failure rate was 7% for nondiabetics and 9% for diabetics, higher than we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…However, these indexes use different ICD codes for diabetes with and without complications. In a cohort of diabetic and nondiabetic hand infections treated as outpatients, Qasawa et al found a low rate of outpatient failure [ 14 ]. Their failure rate was 7% for nondiabetics and 9% for diabetics, higher than we reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are influenced by a significantly reduced number of hospital admissions during the pandemic and an increase in provision of the service allowing for the administration of outpatient intravenous antibiotics. Qasawa et al (2021) reported a case series of 108 hand patients with diabetes treated in an outpatient setting. They demonstrated that 42% of patients with diabetic hand infections were treated successfully by 2 weeks of intravenous antibiotics and bedside debridement.…”
Section: Discussionmentioning
confidence: 99%